La faim et la mort dans la littérature orale montagnaise - Savard, Rémi (Anthropologica, 2022)
The two Montagnais Trickster myths analysed in this paper belong to a set of considerations related to the seasonal cycle and to the dialectic of famine and good life. Within the framework of Montagnais modes of production, they can be interpreted as a symmetrically inverted mechanism controlling distribution of essential resources between competing forces: the wolverine on the one hand (unsocialized hunter) and the Montagnais (socialized hunter) on the other.